MOTIVASI DAN KINERJA - Jurica Lucyanda (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2007)
The role of motivational processes in determining a worker’s level performance is now widely recognized by industrial psychologists. Viteles (1953) has identified the development of the ’’will to work